If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4s + -1s + 3 = 9 Reorder the terms: 3 + 4s + -1s = 9 Combine like terms: 4s + -1s = 3s 3 + 3s = 9 Solving 3 + 3s = 9 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 3s = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 3s = 9 + -3 3s = 9 + -3 Combine like terms: 9 + -3 = 6 3s = 6 Divide each side by '3'. s = 2 Simplifying s = 2
| k/3-11=16 | | 5x+37=72 | | 16x^2+187x+487=11x | | (8x-8)/(x-1) | | -70=-33-k | | 5+2Iog(x)=17 | | -27*20w=73 | | 9(2x+3)=3(5x+9)+3x | | -11+10(1p+10)=4-5(2p+11) | | 9w^2+21w+10= | | 17n-16n=12 | | 1.5x-2.3x=-8 | | -4p= | | 17+8-20=4a-28-3 | | c3=216/343 | | 78=5y+23 | | 4d-3=2d+7 | | 18x+6(4-6)=72 | | 7x^2+46x+55= | | 35x=500+25x | | 6x=6x-33 | | -2j=3(3j-20)-17 | | 20x^2+42x+16=0 | | (210+-2y)-(2y-30)=180 | | -4x+1+6x+2= | | f(x)=x^4-2x^2+3 | | 16t=-8(-t+13)+8 | | 4+12b=100 | | 3a^2+37a-169=37a-13a^2 | | 8(6n+4)=-19-3n | | y-7/8x-14 | | 4x-5+2x=8-2x+11 |